FEATURES OF THE CLINICAL COURSE OF MYOCARDIAL INFARCTION WITH CHRONIC HEART FAILURE IN PATIENTS AT YOUNG AGE (World Bulletin of Public Health, 2023)
In this scientific work, assessment of the clinical status of patients with myocardial infarction with CHF with reduced left ventricular ejection fraction (CHF-SFV) at a young age and its relationship with other factors. The study included 92 patients (45 men, 47 women) with CHF-NFV I-II A stages, according to NYHA I-III FC, in combination with coronary heart disease (CHD), aged 18- 45 years (mean age 35.0± 7.8 years old), hospitalized in the Department of ACS and IHD of the Samarkand Regional Branch of the Republican Scientific and Practical Specialized Medical Center for Cardiology. All patients underwent anamnesis, anthropometry, general clinical examination with an assessment of CHF symptoms according to the SHOKS scale. Exercise tolerance was determined using the 6-minute walk test (WST). ECG and echocardiography were also performed according to the standard method. Women with unstable angina pectoris most often suffer from CHF–SFV, the vast majority of whom have AO. With an increase in the total score for SHOKS, the quality of life and exercise tolerance deteriorate.